Pure early zygotic genes in the Asian malaria mosquito Anopheles stephensi - Yang Wu (Parasites & Vectors, 2018)
Abstract Background The Asian malaria mosquito, Anopheles stephensi, is a major urban malaria vector in the Middle East and on the Indian subcontinent. Early zygotic transcription, which marks the maternal-to-zygotic transition, has not been systematically studied in An. stephensi or any other Anopheles mosquitoes. Improved understanding of early embryonic gene expression in An. stephensi will facilitate genetic and evolutionary studies and help with the development of novel control strategies for this important disease vector. Results We obtained RNA-seq data in biological triplicates from four early An. stephensi embryonic time points. Using these data, we identified 70 and 153 pure early zygotic genes (pEZGs) under stringent and relaxed conditions, respectively. We show that these pEZGs are enriched in functional groups related to DNA-binding transcription regulators, cell cycle modulators, proteases, transport, and cellular metabolism. On average these pEZGs are shorter and have less introns than other An. stephensi genes. Some of the pEZGs may arise de novo while others have clear non-pEZG paralogs. There is no or very limited overlap between An. stephensi pEZGs and Drosophila melanogaster or Aedes aegypti pEZGs. Interestingly, the upstream region of An. stephensi pEZGs lack significant enrichment of a previously reported TAGteam/VBRGGTA motif found in the regulatory region of pEZGs in D. melanogaster and Ae. aegypti. However, a GT-rich motif was found in An. stephensi pEZGs instead. Conclusions We have identified a number of pEZGs whose predicted functions and structures are consistent with their collective roles in the degradation of maternally deposited components, activation of the zygotic genome, cell division, and metabolism. The pEZGs appear to rapidly turn over within the Dipteran order and even within the Culicidae family. These pEZGs, and the shared regulatory motif, could provide the promoter or regulatory sequences to drive gene expression in the syncytial or early cellular blastoderm, a period when the developing embryo is accessible to genetic manipulation. In addition, these molecular resources may be used to achieve sex separation of mosquitoes for sterile insect technique.